Remote vs. local control on the Preboreal Asian hydroclimate and soil processes recorded by an annually-laminated stalagmite from Daoguan Cave, southern China. (15th September 2017) - Liu, Dianbing; Wang, Yongjin; Cheng, Hai; Edwards, R.L.; Kong, Xinggong
Abstract: Stable isotopic measurements on the upper 168 cm of stalagmite DG24 from southern China, which is annually-laminated above 74.8 cm (∼11.8 ka), reconstruct a history of detailed Asian summer monsoon (ASM) variability and soil processes between 14.8 and 10.3 ka. The climate sequence of Bølling-Younger Dryas (YD)-Preboreal events is evident in δ 18 O record. In the Preboreal, four-year-resolution and annually-counted δ 18 O record reveals that the ASM strengthening can be divided into three phases, with a prominent and persistent rise initiated at about 11.2 ± 0.3 ka, likely in response to interactions between ocean, atmosphere, and ice sheets. In contrast, the long-term δ 18 O depletion is absent in the δ 13 C and annual layer records, which characterize persistent centennial oscillations and likely represent relative humidity of the soil. At multi-decadal scale, prominent ASM failures are generally consistent with periods of δ 13 C enrichment and decreased layer thickness. When compared with solar proxies, centennial-scale δ 13 C changes match well with solar activity regardless of the observed disparity between ASM and solar records, and common cycles of 130 and 300 years are identified in both the atmospheric Δ 14 C and speleothem δ 13 C records. This implicates that during the Preboreal local soil humidity budget and CO2 production, indicated by the δ 13 C and annual layer records, is more sensitive to changes in solar output than the regional hydroclimate variability recorded by the δ 18 O signal. Highlights: Four-year-resolution and annually-counted Asian summer monsoon (ASM) variability and soil processes during the Preboreal. A strong resemblance of centennial-scale changes in layer width and δ 13 C record. Abrupt ASM strengthening at 11.2 ± 0.3 ka consistent with sea- atmosphere-ice sheet response at 10.8 ka. Strong coherence of solar activity and δ 13 C record at centennial scale. New insights into remote and local control on soil processes and ASM variability.